On the Relation between Coherence Relations and Anaphoric Demonstratives in German - Kaiser, Elsi (Proceedings of Sinn und Bedeutung, 2019)
Recent research suggests that pronoun interpretation is guided by the semantic coherence relations between clauses. However, it is not yet wellunderstood whether coherence effects extend to other anaphoric expressions beyond pronouns. We report an experiment on German, a language in which human antecedents can be referred to both with personal and demonstrative pronouns. How do anaphoric demonstratives – whose referential properties have been argued to be complementary to pronouns – fit into coherence-based views? Our results suggest that although coherence does not modulate the antecedent choice of anaphoric demonstratives to the same extent that it influences pronoun interpretation, demonstratives interact with coherence-related processing by guiding comprehenders’ expectations of coherence relations.